Dosimetry for photobiomodulation therapy: response to Sommers et al - Khan, Imran; Arany, Praveen R. (Annals of Translational Medicine, 2016)
In a recent article by Sommer et al. in Annals of Translational Medicine, the authors make several key comments on our recent article in Scientific Reports entitled “Molecular pathway of near infrared laser phototoxicity involves ATF-4 orchestrated ER stress” (1). Firstly, we would like to thank the authors for their laudatory, constructive comments, specifically appreciating the rigorous effort and potential impact of our work. However, this editorial also raised a few key issues regarding methodology and interpretations in our study. We feel these points could be further clarified for the increasingly enthusiastic audience following nuances of photobiomodulation (PBM) therapy.